A Gaudium et Spes e a Evangelii Gaudium : um estudo comparativo na perspectiva da conversão pastoral - Colletto, Raquel Maria de Paola (2015)
The reseach faces to the Church’s present situation that feels very difficult to transmit the faith to new generations. It lives itself in a time of profound changes. It proves true that the crisis in contemporary society and ecclesiastical crisis are not dichotomized, but they are as a matter of fact inwardly related. It is underlying in the Vatican II Council’s documents (1962-1965), the need evangelization that leads to a renewed missionary effort. That process is present throughout the post council context until today. In the Latin America, the relevance of a new evangelization inspires itself in the light of Latin America Episcopate’s General Conference. The Aparecida Document emphasizes the seriousness of the moment, calling together all people in the Church to assume positions of pastoral conversion permanent, which it implies to discern what the “Holy Spirit is saying to the Churches”. (Ap 2,29). Therein, the Pope Francisco’s Evangelii Gaudium apostolic exhortation considers the need of an urgent ecclesial renewal (EG 27), detaching the parochial renewal. The theme in Brazil is abovementioned in the documents: Church’s Evangelizing Action Guidelines in Brazil and in the Community of Communities: a new parish: the pastoral conversion of the parish. In that study intends itself to answer as the Gaudium et Spes and the Evangelii Gaudium apostolic exhortation, compare, they can guide the Christian faith transmission in the contemporary world. The analysis is performed relating those two documents from different historical moments. It follows suggesting ways for the Church to continue transmitting with happiness the Gospel in the Vatican II Council perspective.